Effects of TND1128 (a 5-deazaflavin derivative), with self-redox ability, as a mitochondria activator on the mouse brain slice and its comparison with β-NMN - Nanae Takahashi; Norio Akaike; Tomohisa Nagamatsu; Hiroyuki Uchino; Yoshihisa Kudo (Elsevier, 2023)
We have no definitive treatment for dementia characterized by prolonged neuronal death due to the enormous accumulation of foreign matter, such as β-amyloid. Since Alzheimer's type dementia develops slowly, we may be able to delay the onset and improve neuronal dysfunction by enhancing the energy metabolism of individual neurons. TND1128, a derivative of 5-deazaflavin, is a chemical known to have an efficient self-redox ability. We expected TND1128 as an activator for mitochondrial energy synthesis. We used brain slices prepared from mice 22 ± 2 h pretreated with TND1128 or β-NMN. We measured Ca2+ concentrations in the cytoplasm ([Ca2+]cyt) and mitochondria ([Ca2+]mit) by using fluorescence Ca2+ indicators, Fura-4F, and X-Rhod-1, respectively, and examined the protective effects of drugs on [Ca2+]cyt and [Ca2+]mit overloading by repeating 80K exposure. TND1128 (0.01, 0.1, and 1 mg/kg s.c.) mitigates the dynamics of both [Ca2+]cyt and [Ca2+]mit in a dose-dependent manner. β-NMN (10, 30, and 100 mg/kg s.c.) also showed significant dose-dependent mitigating effects on [Ca2+]cyt, but the effect on the [Ca2+]mit dynamics was insignificant. We confirmed the mitochondria-activating potential of TND1128 in the present study. We expect TND1128 as a drug that rescues deteriorating neurons with aging or disease.